Cibercultura, comunicação-dispositivo e dependência: oikonomia em tempo real e disponibilidade do humano na era da mobilidade glocalizada - Barbosa, Bárbara Conceição de Oliveira (2013)
This thesis analyzes humans connection with interactive mobile communication media in the social-historical context of cyberculture, understood as the material, symbolic and imaginary configuration of a time resulting from the technological transformations that took place in the second half of the 20th century. The main objective of the reflection is to understand the logic of mobility endowed with info-technological support in its close interconnection with the phenomenon of obliterated structural dependence. We seek to chart and explain the causes and implications of the context of individuals coupling, and also to question their condition within this civilizing process. The problem implied is that of the independence of subjects undergoing processes of increasingly intense connection with machines; these processes remain in the pre-symbolic plane, not presenting themselves socially as structural dependence. As the main hypothesis of this work, we consider that the urgent need to live in a condition of mobility widely infused with real-time connection is due to the management and control of urgent needs that are fed and executed on a long-lasting basis within mobile interactive contexts, although this does not consciously constitute obedience to the rules of the cybercultural regime. The research is based on the ideas of Bauman, Harvey, Jameson, Lyotard (post-modernity); Breton (communication utopia); Baudrillard and Sfez (regarding the self-referential aspect of communication); Virilio (sociodromology); Trivinho (cyberculture, cybercultural dromocracy and global phenomena); Bourdieu (the concept of habitus); Baudrillard, Bauman and Lipovetsky (on questions related to the consumer society); Lafontaine, Le Breton, Rüdiger, Sfez and Sibilia (technological imaginary and the human condition in present civilization); Breton and Flusser (artifice and communication), Heidegger and Rüdiger (regarding the issue of technique), among other relevant authors. These concepts and tendencies are articulated by means of a critical reflection based on the phenomenic understanding of the sociocultural and historical processes related to the manner of being of the present mediatic civilization, questioning the condition of the subject within this same civilization. This reflection has enabled the analysis and clarification of factors underlying daily socio-technological experience, inherent especially to the changes brought about by social investment in interactive mobility, contributing also to the development of critical epistemology in the area of Communication, in the field of studies of the media and computer networks in their present configuration